Understanding Early Childhood Education Quality Through Political, Economic, Social, and Cultural Lenses - Saugi, Wildan; Novarita, Novarita; Warman, Warman; Bahzar, Moh.; Nurlaili, Nurlaili (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
This systematic literature review synthesizes 29 studies published between 2016 and 2025 to examine the multidimensional factors shaping the quality of early childhood education (ECE) across global contexts. Findings show that ECE quality is influenced by six interrelated dimensions: inclusion, equity, funding, wellbeing, governance, and culture, which interact through broader political, economic, social, and cultural structures. Strong governance and sustainable financing enhance equitable access, while inclusive and culturally responsive pedagogies support children’s holistic development and socio-emotional wellbeing. The review also identifies fragmentation across studies, limited cross-country comparative work, and persistent policy-practice gaps that hinder the effective implementation of high-quality ECE. The study proposes an integrated model demonstrating how structural and contextual factors collectively shape early learning experiences. These insights provide a foundation for strengthening policy alignment, professional development, and culturally grounded practices to improve ECE quality worldwide.